ANALISA STRUKTUR VISUAL SEBAGAI DASAR PEMBENTUKAN KEYWORD VISUAL DARI SEBUAH FILM ANIMASI - Ristia Kadiasti Kadiasti; Nita Virena Nathania; Toto Haryadi (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2023)
The design of an animated film of both 2D, 3D and Stop Motion types has a significant pre-production stage with the design of story ideas and visualization which will later be applied to the finalization of the animation work. This visualization cannot be separated from how the story structure will build the overall form of the animated film. Visual Structure Theory from Bruce Block helps organize visual patterns using storytelling graphics in the form of color scenarios as a reference from samples of the Coco film and Spirited Away films which have stories with spiritual and magical themes but inherently different cultural backgrounds. This research will find the visual structure patterns of the two animated film samples to become a reference for the formation of a visual keyword in the design of animated films